Skrining Lansia dan Pelatihan Caregiver Berbasis Academic Practice untuk Penguatan Layanan dan Kompetensi Mahasiswa di Griya Kasih Siloam Malang: Elderly Health Screening and Caregiver Training through an Academic Practice Approach to Strengthen Health Services and Nursing Students’ Competencies at Griya Kasih Siloam, Malang - Annisa Wuri Kartika; Yati Sri Hayati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Health services for older adults in residential care facilities require a holistic approach encompassing promotive, preventive, curative, and rehabilitative aspects. At Griya Kasih Siloam Elderly Care Home in Malang, health services are still primarily focused on meeting basic needs and rely heavily on external healthcare partners, underscoring the need to strengthen services through the integration of healthcare delivery and nursing education. The integration of service and academic activities is also essential to enhance students’ competencies, particularly therapeutic communication skills that are responsive to the characteristics of older adults. This community service program aimed to improve promotive and preventive health services through collaboration between educational institutions and elderly care facilities. The activities included health examinations, training in dementia care for caregivers, student-led elderly companion visits involving group interventions such as music therapy and cognitive therapy, and evaluation and follow-up. The activities were conducted over four sessions involving 90 students, older adults, and caregivers at Griya Siloam. Pre-test and post-test results demonstrated an increase in caregivers’ knowledge (n = 5) regarding dementia care, with mean scores improving from 62.5 to 88.5. In addition, student survey results (n = 90) indicated an 82% improvement in understanding and therapeutic communication skills with older adults, particularly in empathy and communication clarity. This program suggests the importance of interdisciplinary collaboration involving nutrition, physiotherapy, and psychology to enrich interventions and ensure truly holistic services tailored to the needs of older adults.